Діалектна мапа Львівщини - Ястремська, Т. (Культура слова, 2018)
Львівщина – особливий діалектний простір, який поєднує чотири говори південно-західного наріччя української мови – наддністрянський, надсянський, бойківський та волинський (південноволинські говірки). У статті проаналізовано особливості дослідження цих говорів, а також активовано одну з найважливіших проблем діалектології та лінгвогеографії – визначення меж говорів та смуг перехідних говорів. На підставі праць діалектологів від кінця ХІХ до початку ХХІ ст. та сучасних експедиційних записів Н. Хібеби, Л. Хомчак, В. Шелемех (Різник), Т. Ястремської та ін. уточнено межі говорів, які демонструє картосхема. Lviv region is a unique dialect space. There are four dialects of the South-Western dialect of the Ukrainian language, namely, Dniester dialects, Sian dialects, Bojkian dialects, and South Volhynian dialects. The peculiarities of the study of these dialects, the underlying theoretical works, the achievements of lexicography and linguogeography analysed in the article. The problem of division of the dialects is one of the most important in dialectology. First of all, it relates to the fact that a sharp transition between the dialects there, mostly fix transition zones dialects, whose presence proves impossible to draw a clear boundary between adjacent dialects. The conventional dialect boundaries, including zones of transition, were allocated in the article. Based on existing studies analysed dialects, as well as modern records dialect speech by the N. Khibeba, L. Khomchak, V. Shelmekh (Riznyk), T. Yastremska and others.